Archaeobotanical reconstructions of field habitats and crops: the grange in Pomorzany near Kutno, 18th/19th c. - Koszałka, Joanna; Strzelczyk, Joanna Ewa (Biodiversity: Research and Conservation, 2015)
The paper presents the results of research of plant macrofossils from the grain deposit deriving from the 18th/19th centuries. The analysed material included 24760 diaspores representing 73 taxa. The majority were cultivated cereal crop species, and there was also abundance of accompanying segetal weed species. About 95% of the gathered crop material was Secale cereale. Another important crop was Hordeum vulgare and there were also some remains of Avena sativa, Triticum aestivum, Fagopyrum esculentum. Cannabis sativa and Linum usitatissimum were found as well. Weeds competing with these crops were, among others, the following species: Agrostemma githago, Raphanus raphanistrum, Apera spica-venti, Bromus secalinus, Centaurea cyanus, Spergula arvensis, Thlaspi arvense, Viola arvensis/tricolor, Fallopia convolvulus, Polygonum persicaria, Mentha arvensis, Anthemis arvensis, Papaver rhoeas, Rumex acetosella, Scleranthus annuus, Aphanes arvensis, Setaria pumila, Setaria viridis/verticilata. Extremely large presence of wild plant diaspores in the material allowed conducting economic and environmental interpretations. Reconstruction methods applied, used primarily in the case of macroremains from granaries, were fully applicable to the analysed plant residues. Weed species composition in the analysed material showed that they were mostly typical for the main winter crop. Some amount of species typical for other habitats were also found and they probably came from the near-by rye field. The presence of perennial diaspores indicated that the field was probably set aside